The power balance of the dc traction substation at the different levels of the voltage unbalance of the external power supply system - Земський, Денис Романович; Босий, Дмитро Олексійович (Eastern-European Journal of Enterprise Technologies, 2014)
This article contains the research of DC traction substation power balance and the components of the apparent power for the DC and the AC circuits in the normal and the unbalanced modes. The ratio of higher harmonics of DC voltage which depends on the external voltage unbalance is used for the quantitative estimation of the external network influence on the rectifier. The cause of the research lies in need of the energy saving with regard to the power quality which needs power balance evaluation. Many authors suppose that in the DC traction system the conversion process from the three-phase energy to the DC energy is symmetrical but in fact the voltage unbalance creates additional difficulties for the power supply devices and might be considered. The result of research is in determination of the fact that changing voltage unbalance doesn’t change the three-phase and the DC power factors. While the voltages unbalance is reallocating the power in phases of the rectifier the power factor is increasing in the phase with lower voltage and decreasing in the other phases. The importance of the given result is in the method of voltage unbalance definition with the higher harmonics ratio that allows the accurate calculation only by the values of DC harmonic magnitudes. In practice the given method allows to avoid the measurement of the primary networks parameters in the control systems. The created physical model may be useful for the further research of the DC traction substation in parts of creating and tuning the devices of the power quality improvement.